Some comments on THE ICILA DANCE OLD STYLE by A. M. Jones and L. Kombe, published by Longmans Green for the African Music Society, 1952, 49 pp. - Clausen, Raymond; Rycroft, David K. (International Library of African Music, 1954)
pages: 92
Keywords: African Music